2020
DOI: 10.1039/c9me00148d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymer–nanoparticle interactions on solvent-driven infiltration of polymer (SIP) into nanoparticle packings: a molecular dynamics study

Abstract: Dynamics of polymer motion into solvent-filled interstices of nanoparticle packings can be controlled by tuning the polymer–nanoparticle interactions, whose effect on the rate of infiltration is non-monotonic as shown by MD simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Future work will focus on probing how tuning the strength of the polymer–surface interaction impacts the dynamics of infiltration in the SIP system and the final extent of infiltration. Molecular dynamics simulations on the SIP system have found that by inducing stronger adhesion between the polymer and NP, a transition from dissolution-dominated infiltration to adhesion-dominated infiltration occurs . Our future work will probe experimentally how altering the nature of the surface interactions affects the extent of infiltration and the infiltration dynamics.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Future work will focus on probing how tuning the strength of the polymer–surface interaction impacts the dynamics of infiltration in the SIP system and the final extent of infiltration. Molecular dynamics simulations on the SIP system have found that by inducing stronger adhesion between the polymer and NP, a transition from dissolution-dominated infiltration to adhesion-dominated infiltration occurs . Our future work will probe experimentally how altering the nature of the surface interactions affects the extent of infiltration and the infiltration dynamics.…”
Section: Discussionmentioning
confidence: 92%
“…Molecular dynamics simulations on the SIP system have found that by inducing stronger adhesion between the polymer and NP, a transition from dissolution-dominated infiltration to adhesion-dominated infiltration occurs. 45 Our future work will probe experimentally how altering the nature of the surface interactions affects the extent of infiltration and the infiltration dynamics. To better understand partitioning and kinetics in such systems, an entropic barrier model using self-consistent field theory simulations is currently being investigated.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…suggest, the imbibition proceeds as an adhesion‐dominated process whereby the polymers move into the pores as a diffuse front of polymer chains progressing at different rates. [ 53 ] However, the authors suggest that the speed of infiltration is considerably slower for large polymers. This leaves the question of how the pore structure influences important parameters such as the surface tension and viscosity of the imbibed liquid.…”
Section: Resultsmentioning
confidence: 99%
“…New preparation modes were recently reported to overcome the various limitations seen in conventional blending regarding the arbitrary distribution of nanoparticles in the polymer matrix, namely vapor condensation, capillary rise infiltration and ink-jetting. [6,7,[11][12][13][14] One of these new methods is based on the preparation of a highly porous nanoparticle scaffold formed by flame spray pyrolysis (FSP) [15] and the infiltration of the pores with a photo-curable monomer. [16] In a second step, the monomer is photo-polymerized under preservation of the initial particle network, forming an inverse NPC.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%